The Epidemiology, Associated Factors and Bacterial Profile of Asymptomatic Bacteriuria in Pregnant Women: A Retrospective Chart Review Study in Saudi Arabia - AlShamlan NA; AlOmar RS; Aldossary R; Alahmari M; Alghamdi A; AlGhamdi M; Alkanaan N; AlReedy AH; AlOtaibi AS; Alghamdi NS (Dove Medical Press, 2022)
Nouf A AlShamlan,1 Reem S AlOmar,1 Roba Aldossary,2 Maha Alahmari,2 Asma Alghamdi,2 Mawaddah AlGhamdi,2 Najla Alkanaan,2 Abdullah H AlReedy,1 Amani S AlOtaibi,3 Nada S Alghamdi4 1Department of Family and Community Medicine, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 3Department of Obstetrics and Gynaecology, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 4Department of Microbiology, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Nouf A AlShamlan, College of Medicine, Imam Abdulrahman Bin Faisal University, P.O. Box 1982, Dammam, 34224, Saudi Arabia, Tel +966504901406, Email nashamlan@iau.edu.saPurpose: Asymptomatic bacteriuria (ASB) is the presence of significant amounts of bacteria within the urinary tract in the absence of urinary tract infection (UTI) symptoms, resulting in negative neonatal and pregnancy consequences. This study determined the prevalence, bacteriology patterns, and associated factors with ASB among pregnant women in both primary and hospital levels of care in the Eastern Province of Saudi Arabia.Methods: This retrospective chart review study included pregnant women between 18 and 50 years who performed the screening urine culture test during their first antenatal visit between 2017 and 2021, without UTI symptoms. The collected data involved the demographic, medical, and obstetric characteristics, and urine culture results. T-tests and chi-squared tests were used for bivariate associations followed by binary logistic regression models.Results: ASB was positive among 03.42% of the 6471 pregnant women included in the study. Logistic regression revealed that the risk of positive ASB increased in pregnant women in the first and second trimesters (OR = 2.04, 95% CI = 1.41- 2.93 and OR= 1.50, 95% CI = 1.03- 2.19, respectively), as well as pregnant women with a history of previous UTI (OR = 2.98, 95% CI = 2.14- 4.15). The predominant organism isolates were E. coli, followed by GBS, Klebsiella pneumoniae, and Enterococcus faecalis.Conclusion: With limited data on ASB among pregnant women in Saudi Arabia, findings from the current study could help decision-makers in the country assess the epidemiological characteristics of the condition. Further study is recommended to investigate the susceptibility patterns of commonly prescribed antibiotics with different uropathogens to guide the clinicians who deal with these cases. Additionally, a large national study across the other regions in the kingdom is suggested to calculate the prevalence of ASB in Saudi Arabia.Keywords: asymptomatic bacteriuria, pregnant, prevalence, E. coli, epidemiology, Saudi Arabia